2019
DOI: 10.1029/2018jb016553
|View full text |Cite
|
Sign up to set email alerts
|

Linking Structural and Transport Properties in Three‐Dimensional Fracture Networks

Abstract: We investigate large‐scale particle motion and solute breakthrough in sparse three‐dimensional discrete fracture networks characterized by power law distributed fracture lengths. The three networks we consider have the same fracture intensity values but exhibit different percolation densities, geometric properties, and topological structures. We considered two different average transport models to predict solute breakthrough, a streamtube model and a Bernoulli continuous time random walk model, both of which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 110 publications
2
61
0
Order By: Relevance
“…However, even in the densest networks at the kilometer scale, we still observe significant difference in tailing between the correlated and fixed tortuosity CTRW models at intermediate CCDF values [0.01,1]. Interestingly, the fixed CTRW underestimated tailing for this same CCDF regime in the fracture networks studied by Hyman et al (2019), although their networks had higher density. This again shows that the velocity-tortuosity correlation structure is important for breakthrough tailing, as slow velocity-large regions delay solute transport.…”
Section: Larger Scale Breakthrough Curve Predictionsmentioning
confidence: 68%
See 1 more Smart Citation
“…However, even in the densest networks at the kilometer scale, we still observe significant difference in tailing between the correlated and fixed tortuosity CTRW models at intermediate CCDF values [0.01,1]. Interestingly, the fixed CTRW underestimated tailing for this same CCDF regime in the fracture networks studied by Hyman et al (2019), although their networks had higher density. This again shows that the velocity-tortuosity correlation structure is important for breakthrough tailing, as slow velocity-large regions delay solute transport.…”
Section: Larger Scale Breakthrough Curve Predictionsmentioning
confidence: 68%
“…The inherent heterogeneous structure of natural fracture networks is characterized by a broad range of lengths, spanning from the aperture roughness to the full network scale Bonnet et al (). At the network scale, the topological properties set the flow field structure (de Dreuzy et al, ; Frampton et al, ; Makedonska et al, ), meaning velocity at the in‐fracture scale is highly correlated (Hyman et al, ; Kang, Le Borgne, et al, ) and subfracture scale features are less important. Complex network topologies naturally result in a very broadly distributed velocity field, which influences associated transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have investigated fluid flow in stressed 3‐D fracture networks (Garipov et al, ; Lei et al, ; McClure et al, ), the effects of geological stress on tracer transport through 3‐D fracture networks remain to be investigated. A recent study has shown that the Bernoulli CTRW model can capture particle transport through 3‐D fracture networks (Hyman et al, ), and the natural extension of this study will be the effects of geological stress on particle transport through stressed 3‐D fracture networks. Finally, since fracture network properties and in situ stress conditions can vary widely from location to location, additional studies are required to obtain more general conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…DFN models represent fractures as discrete entities and enable the study of the effects of fracture geometrical properties on fluid flow and transport explicitly. Fluid flow and transport in DFNs have been the subjects of many investigations over the past decades, and recent advances in computational power have enabled more detailed flow and transport studies in complex three-dimensional (3-D) DFNs with multiscale heterogeneity (Benedetto et al, 2016;Hyman & Jiménez-Martínez, 2018;Hyman et al, 2019;Makedonska et al, 2015;Maillot et al, 2016;Viswanathan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology is based on a Lagrangian approach that allows to identify and quantify the stochastic rules of advective particle motion in disordered media. Similar approaches have been used in previous works for the analysis and upscaling of pore-scale transport (Morales et al 2017;Puyguiraud et al 2019) and for transport in multi-Gaussian hydraulic conductivity fields (Hakoun et al 2019) and fractured media (Hyman et al 2019). Here, we use a Lagrangian approach to gain understanding of the stochastic principles of transport in random composite media through the analysis of advective trapping events in low conductivity inclusions, and the distribution of flow speeds sampled between them.…”
Section: Introductionmentioning
confidence: 99%